Morpho-Functional Characteristics Of Girls Specialized In Neutral Sports - Ramanova Dilfuza Kenjayevna (Genius Publishing Group, 2026)
The study of morpho-functional characteristics in girls specialized in neutral sports is a relevant topic in contemporary sports science and medicine. Neutral sports, which typically involve balanced physical activity focusing on endurance, agility, flexibility, and overall harmonious body development, have a significant impact on the morphofunctional development of young female athletes. The analysis of these characteristics is crucial for optimizing training programs, improving athletic performance, and ensuring the overall health of young sportswomen
Keywords: morpho-functional indicators; neutral sports; specialization; body composition